Pengaruh Gaya Kepemimpinan, Komunikasi Organisasi, dan Disiplin Kerja Terhadap Kepuasan Kerja Pegawai di Kantor Kecamatan Babakan Ciparay Kota Bandung - Hanifah Lestari; Dedi Gumilar (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The importance of human resources in government organizations is closely related to the achievement of its goals. To provide the best service to the public, the Babakan Ciparay District Office in Bandung City, one of the public service organizations, requires employees who are not only skilled but also highly satisfied with their jobs. The average proportion is 19.3%. This indicates that workers at the Babakan Ciparay District Office show signs of job dissatisfaction. The researcher used a descriptive methodology. To test the theory or provide answers to the research issues, descriptive analysis techniques were used. The sample is a portion of the size and composition of the population selected for the study. A non-probability sample with a purposive sampling method is the sampling strategy used in this study. The research findings indicate that organizational communication and leadership style both significantly influence employee job satisfaction. This indicates that employee job satisfaction is significantly influenced by work discipline. Thus, H0 is rejected and Ha is accepted. This indicates that employee job satisfaction at the Babakan Ciparay District Office in Bandung City is significantly and positively influenced by Perception of Work Discipline (X1), Organizational Communication (X2), and Leadership Style (X3) simultaneously.